Effective judicial protection in community law: the role of the Central American Court of Justice of the Central American Integration System - Esquivel Avendaño, Eymi Lissette (DIXI, 2024)
This conceptual research article conceptualizes effective judicial protection within the framework of the Inter-American Human Rights System and the construction of this right in the European Union, through its legal system and the jurisprudence of its Court of Justice. This exercise allows for the delimitation of effective judicial protection within the community framework for analysis from the perspective of the Central American Integration System (SICA) and, specifically, from the jurisdictional competencies of the Central American Court of Justice (CCJ) that can be driven by individuals or by the national judge. Finally, the jurisprudential development of effective judicial protection from the ccj is determined. This confirms the existence of effective judicial protection in the competencies delegated to this supranational body.
Keywords: Central American Court of Justice; community law; human rights; national judge; sica; effective judicial protection